The systems thinker a practical guide to use critical thinking for change your life know yourself through thought patterns view and work on your Behaviors to increase your problem solving Skills - Maidan, Stefan (‎Independently published, 2020)
A useful system to identify a series of relationships that make our social and professional lives harder.
Keywords: Systems